Factors for the development of students ' architectural compositions performance skills - Berdiyev Nurmon Ochilovich (Open Academia, 2023)
This article delves into the multifaceted factors influencing the development of students' architectural composition performance skills. Through a comprehensive analysis of existing literature, the study aims to identify key elements that contribute to the enhancement of these skills. The research employs a mixed-methods approach, combining quantitative and qualitative data to provide a thorough understanding of effective teaching methods and their impact on students' architectural compositions. The results shed light on the intricacies of skill development in design education, offering valuable insights for educators, students, and stakeholders in the field
Keywords: Architectural compositions; performance skills; design education